Hubungan Antara Persepsi Ibu Hamil Tentang Mutu Pelayanan Antenatal Dengan Kepuasan Ibu Hamil Di Puskesmas Krobokan Kota Semarang - Haposanita S., Riama; Patria Jati, Sutopo; Suparwati, Anneke (Jurnal Kesehatan Masyarakat (Undip), 2014)
Maternal health issues and newly born babies in Indonesia is a public health problem that needs major attention, because it has a major impact on the quality of future generations. One of the maternal and child health services are Antenatal care is health care for all pregnant women with a relatively low cost. Antenatal care coverage is not optimal quantity is still below the target of Semarang City Health Office that is 95%, and Krobokan Health Center is one of the centers with the lowest ANC coverage. Based on the preliminary results of a survey conducted in pregnant women in health centers Krobokan through interviews that there is a link between the quality of health services in the form of reliability, responsiveness, tangibles, assurance, empathy with maternal satisfaction. This study aims to determine the relationship between maternal perception of the quality of antenatal care to the satisfaction of pregnant women in health centers Krobokan Semarang. Observational research using survey methods with cross sectional approach, a population of 413 pregnant women with a total sample of 85 respondents. Statistical analysis using chi square. The results showed that the quality of service that consists of responsiveness, tangibles, assurance, empathy, suggests that there is a connection with the satisfaction of pregnant women in health centers and reliability Krobokan has no association with maternal satisfaction. The proposed suggestions to improve the quality of PHC services Krobokan namely the improvement of existing SOPs, standards of antenatal care, and create a policy that officers can improve their skills in work, communication with patients, and also complete the facilities at PHC Krobokan